Wykonaj mnożenia i zredukuj wyrazy podobne:
a) (2x - 1) (x + 4) =
b) (3y – 5)(-y + 2) =
c) (5x – 4)(3 + 2x) =
d) (2x-3)(x²-4x + 5) =
e) ( x² - 2x + 3 )( x - 4 ) =
Pls szybko daje naj​


Odpowiedź :

Hej!

a)

(2x - 1)(x + 4) =

= 2x² + 8x - x - 4 =

= 2x² + 7x - 4

b)

(3y - 5)(-y + 2) =

= -3y² + 6y + 5y - 10 =

= -3y² + 11y - 10

c)

(5x - 4)(3 + 2x) =

= 15x + 10x² - 12 - 8x =

= 10x² + 7x - 12

d)

(2x - 3)(x² - 4x + 5) =

= 2x³ - 8x² + 10x - 3x² + 12x - 15 =

= 2x³ - 11x² + 22x - 15

e)

(x² - 2x + 3)(x - 4) =

= x³ - 4x² - 2x² + 8x + 3x - 12 =

= x³ - 6x² + 11x - 12

Pozdrawiam! - Julka

Viz Inne Pytanie